Performance Analysis of Cooperative Dynamic Framed Slotted-ALOHA With Random Transmit Power Control in A2G Communication Networks - Junseung Lee; Seungmin Lee; Seong Ho Chae; Howon Lee (IEEE Access, 2022)
In this study, we investigate the use of low-altitude unmanned aerial vehicles (UAVs) in air-to-ground (A2G) communication networks, which still have various issues and challenges. In particular, the limited battery power of UAVs render their flight time extremely short. Hence, we present cooperative dynamic framed slotted-ALOHA (CDFS-ALOHA), which is capable of random transmit power control (TPC). When collisions occur, because UAVs can select their retransmit power randomly, their power consumption is reduced and their probability of successful packet transmission is improved owing to a capture effect. In terms of performance metrics, we consider the successful packet transmission probability, UAV power consumption, and network-wide energy efficiency. CDFS-ALOHA with TPC can directly reduce the transmit power consumption of UAVs compared to CDFS-ALOHA without TPC; thus, intra- and intercell interference can be reduced. Consequently, CDFS-ALOHA with TPC can obtain sporadic and intermittent capture effects, thus improving the network-wide energy efficiency without reducing the probability of successful packet transmission in A2G communication networks.